2019
DOI: 10.1017/s0959270919000352
|View full text |Cite
|
Sign up to set email alerts
|

Long-term declines in common breeding seabirds in Japan

Abstract: SummaryGlobal seabird populations are in decline, with nearly half of all seabird species currently in an extinction crisis. Understanding long-term seabird population trends is an essential first step to inform conservation actions. In this study, we assembled historical breeding records of seabirds throughout the Japanese archipelago and quantified the long-term population trends of 10 major breeding seabird species using a hierarchical Bayesian state-space model. The model revealed that six species had incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…They are currently listed as special concerns in California, as sensitive in Oregon, as endangered in Washington, and as imperiled in British Columbia (Hanson et al 2019). Additionally, this species has been in decline in Japan since the 1970s (Senzaki et al 2020). It has been suggested that population declines have occurred in response to rising ocean temperatures, which are thought to have shifted forage fish composition and distribution in the region (Jones et al 2019, Pearson et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…They are currently listed as special concerns in California, as sensitive in Oregon, as endangered in Washington, and as imperiled in British Columbia (Hanson et al 2019). Additionally, this species has been in decline in Japan since the 1970s (Senzaki et al 2020). It has been suggested that population declines have occurred in response to rising ocean temperatures, which are thought to have shifted forage fish composition and distribution in the region (Jones et al 2019, Pearson et al 2023).…”
Section: Introductionmentioning
confidence: 99%